2016
DOI: 10.1111/faf.12143
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐taxa assessment of pelagic longline by‐catch mitigation measures: conflicts and mutual benefits to elasmobranchs

Abstract: Elasmobranch mortality in pelagic longline fisheries poses a risk to some populations, alters the distribution of abundance between sympatric competitors, changing ecosystem structure, processes and stability. Individual and synergistic effects on elasmobranch catch and survival from pelagic longline gear factors, including methods prescribed to mitigate bycatch of other vulnerable taxa, were determined. Overall relative risk of higher circle vs. J-shaped hook shark catch rates conditioned on potentially infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 112 publications
(410 reference statements)
11
97
0
Order By: Relevance
“…However, regulations requiring use of fish bait to reduce sea turtle bycatch must be balanced against the potential target species catch loss, a concern that has been previously evaluated (Watson et al, 2005;Yokota et al, 2009;Curran and Bigelow, 2011;Coelho et al, 2012). Further, bait choice can also potentially increase bycatch of certain sharks or other vulnerable species (Foster et al, 2012;Santos et al, 2012;Gilman et al, 2016b). As with other bycatch reduction techniques, success in adopting these measures may be fishery dependent.…”
Section: The Role Of Bait In Bycatchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regulations requiring use of fish bait to reduce sea turtle bycatch must be balanced against the potential target species catch loss, a concern that has been previously evaluated (Watson et al, 2005;Yokota et al, 2009;Curran and Bigelow, 2011;Coelho et al, 2012). Further, bait choice can also potentially increase bycatch of certain sharks or other vulnerable species (Foster et al, 2012;Santos et al, 2012;Gilman et al, 2016b). As with other bycatch reduction techniques, success in adopting these measures may be fishery dependent.…”
Section: The Role Of Bait In Bycatchmentioning
confidence: 99%
“…Several studies and symposiums have evaluated the effectiveness of circle hooks across and found that reductions are not necessarily achieved for all non-target bycatch species taxa (Kerstetter and Graves, 2006;Serafy et al, 2012;Huang, 2015). In some cases, circle hooks may increase bycatch of sharks (see Gilman et al, 2016b). There is a clear need for further investigation of cross-taxa bycatch solutions in pelagic longline fisheries.…”
Section: Ecosystem Level Impacts Of Findingsmentioning
confidence: 99%
“…The immediate mortality of incidentally caught sharks can be substantial (Dapp et al, 2016a), and incidental capture has been identified as a major driver of declines in shark populations (Dulvy et al, 2014). Immediate mortality rates of sharks during longline capture can be influenced by a multitude of factors, such as, but not limited to, capture duration, hook type, hook size, species-specific biology, and crew-specific handling practices (Campana et al, 2009;Morgan and Carlson, 2010;Dapp et al, 2016aDapp et al, , 2016bGilman et al, 2016). Factors contributing to the immediate mortality of sharks caught by the U.S. Atlantic pelagic longline fishery have previously been examined by using the data set of the National Marine Fisheries Service (NMFS) Pelagic Observer Program (POP) (Serafy et al, 2012;Gallagher et al, 2014).…”
Section: Noaamentioning
confidence: 99%
“…Although this rule was implemented to reduce bycatch mortality of species of turtles (NMFS 2 ), circle hooks are less likely than traditionally used Jhooks to be swallowed by some species of shark. The use of these hooks, therefore, reduces occurrences of internal injuries and immediate mortality rates in some species (Kerstetter and Graves, 2006;Campana et al, 2009;Serafy et al, 2012;Gilman et al, 2016;but see Yokota et al, 2006). In accordance with the methods of Serafy et al (2012), we considered only specific regulatory periods in our analysis.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation